2007
DOI: 10.1007/s10533-007-9087-1
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic review of the genus Phaeocystis

Abstract: Phaeocystis is recognized both as a nuisance and as an ecologically important phytoplankton species. Its polymorphic life cycle with both colonial and Xagellated cells causes many taxonomic problems. Sequence variation among 22 isolates representing a global distribution of the genus has been compared using three molecular markers. The ribulose-1,5-bisphosphate carboxylase/oxygenase (RUBISCO) spacer is too conserved to resolve species. The most conserved 18S ribosomal deoxyribonucleic acid (rDNA) analysis sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…Overall, our results are consistent with previous studies showing that species of Phaeocystis occurring in polar and non-polar areas are distinct (Schoemann et al 2005, Decelle et al 2012. Few studies have reported blooms of P. jahnii and P. cordata, which may be due to their small size, or may indicate that they cannot form, or seldom form, colonies in the natural environment (Zingone et al 1999, Medlin & Zingone 2007. Molecular approaches appear to be useful tools for studying the distributions of P. jahnii and P. cordata.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our results are consistent with previous studies showing that species of Phaeocystis occurring in polar and non-polar areas are distinct (Schoemann et al 2005, Decelle et al 2012. Few studies have reported blooms of P. jahnii and P. cordata, which may be due to their small size, or may indicate that they cannot form, or seldom form, colonies in the natural environment (Zingone et al 1999, Medlin & Zingone 2007. Molecular approaches appear to be useful tools for studying the distributions of P. jahnii and P. cordata.…”
Section: Discussionsupporting
confidence: 92%
“…Sequences most similar to P. jahnii have also been found in the Ross Sea by Gast et al (2004). It seems that the genus Phaeocystis is more diverse than presumed, which Medlin and Zingone (2007) also illustrated by reviewing the genetic variation of 22 isolates. Furthermore, it is possible that Phaeocystis has different ecotypes that are able to cope with a wide range of environmental conditions.…”
Section: Community Compositionmentioning
confidence: 82%
“…This is particularly true for taxa for which classification was previously controversial due to the lack of clear morphological criteria. Successful integration of morphological and molecular taxonomy has been demonstrated for many groups of marine flagellates, for example, for cryptomonads (Hoef-Emden & Melkonian, 2003;Cerino & Zingone, 2006, 2007 and prymnesiophytes (Edvardsen et al, 2000;Medlin & Zingone, 2007;Edvardsen et al, 2011). Nevertheless, attempts to achieve such a synthesis with raphidophytes have thus far been more problematic, mainly because of the lack of correspondence between morphological and molecular classifications.…”
Section: Discussionmentioning
confidence: 99%